Women's participation in the prevention and control of dengue using environmental methods in the global south: a qualitative meta-synthesis - Cathy Mungall-Baldwin (BMC, 2022)
Abstract Background Dengue, a mosquito-borne viral disease, causes significant mortality and morbidity in low- to middle-income countries. A body of research indicates that women can be effective in implementing vector borne disease control, but they still face inequitable opportunities for participation, leadership and decision-making in the execution of dengue prevention and vector control programmes. Yet implementing informal environmental management practices to prevent mosquito vector breeding forms part of their domestic household responsibilities. Understanding the enablers and barriers to women's equitable roles with men in formal and informal disease prevention, and the benefits of their participation could help to increase their role and may be a contributing factor to reducing disease rates. The objective of this qualitative meta-synthesis was to synthesise evidence about women's roles in dengue prevention and control in the global south and generate insights around the barriers, enablers, and benefits. Methods Eight databases were searched from inception to 7th December 2020. One investigator independently reviewed all titles and abstracts for relevant articles. Grey literature was searched using 34 websites of global health and international development organisations. Results A total of 18 articles representing qualitative research or the qualitative component of mixed methods studies from Latin American and Caribbean (n = 8), Asia (n = 9), and one international review were included in the meta-synthesis. Relevant scholarship from Africa was lacking. This meta-synthesis revealed five unique themes surrounding women's participation, seven categories of barriers, six of enablers, four health, well-being and social benefits for individuals, and four for communities . Conclusion An analysis of the results confirmed that women's participation in dengue prevention was not gender equitable, gender sensitive nor transformative although women are the primary human resource for household and community-based prevention. Women demonstrated specific qualities aiding successful implementation. Corrective action is urgently needed to shift unhelpful gender norms, and empower women into leadership and decision-making roles.